Environment mapping, map constructing, and path planning for underwater navigation of a low-cost µAUV in a cluttered nuclear storage pond - Yibin Peng; Peter N. Green (IAES International Journal of Robotics and Automation (IJRA), 2019)
This paper presents a novel approach that enables a low-cost µAUV (micro autonomous underwater vehicle) navigate and work safely in an enclosed cluttered underwater environment. In order to achieve a autonomy collision-free navigation in underwater, it requires a reliable approach that would allow a µAUV which equipped with sparse and inaccurate sonar sensors to map the underwater environment, a map constructing algorithm that converts the obtained data to useful information to establish a map, and a path planning algorithm that plans a collision-free path from the start to the desired goal. The proposed approach will integrate environment survey, environment reconstruction, and path planning as a completed task, which involves map acquisition and path planning. A complete simulation of the environment topology acquisition and route planning process is documented in this paper.